Assessment Of Computer Managed Instruction For IMO State University, Nigeria (International Journal of Engineering and Computer Science, 2015)
Computer Managed Instruction(CMI) is a Computer Software whose primary purpose is teaching or self learning.This paper was motivated by the fact that Imo State University is under pressure to deliver an efficient and effective teaching process but constraints on staffing with increasing number of students have brought about unfavourable situations in most departments such that problem solving lectures have been an uphill task. This paper therefore seeks to investigate whether the use of Computer Managed Instruction (CMI) has impact on the learners. The methodology involved collection of Data through questionnaires and statistically analyzed using the Weighted Mean Average. The result showed among others that those who use Computer Managed Instruction learn faster and better than those who use the classroom Face me, I Face you learning, also showed the Computer Managed Instruction is an effective aid in the teaching/Learning process.